Retenção de água da chuva na palha, solo e dossel vegetativo de milho e feijão - Fontana, Vanessa Schwanke (2007)
The water is the most important factor and, at the same time, the more limitant than the plant needs for its development. Short periods of hidric stress can reduce crop productivity. In this way, the importance of knowing the rainfall amount that is retained in plant, straw and soil is fundamental to calculating the exact amount of water requested by the plant in their different growth stages. The objective of this work was to determine the water retention in the straw, in the soil and in the plants dossal after a precipitation, in the initial phase of growth of corn and bean crops. The drybeans (cv Rio Tibagi) and corn (hybrid Pioneer 30R53) were sowed in no-till (2, 4 and 6 t straw ha-1) and conventional (0 t of straw in covering) during 2006 agricultural year. The experimental design for corn was a bifatorial (2x4) and 3 replications, and for bean was a factorial and 3 replications. For corn two row spacings were tested (45 and 75 cm). Artificial rains were applied using a portable simulator of multiple nozzles, which applied 4 to 8 mm, with 30 mm h-1 rain intensity. They were made ridges in the area, (with steepness to drain the water) and a plastic canvas covered the soil surface, so that water that arrived to the plastic drained for the surface until a collector placed among two plants rows. Straw rugs were made with different amounts of straw (0, 2, 4 and 6 t ha-1) and put among the plants rows above soil surface (plastic canvas). The determination of the amount of water retained was made through the differences of weightings. The amount of applied water with the simulator was known using pluviometers; the straw rugs were weighed before and after rain simulation (for difference, it was obtained the value of water retention in straw). The water that passed through straw and was drained until the plastic was collected after the rain, in the collector placed between the plants lines and measured with a test tube, and obtained the amount of water that arrived to the soil, that in practice corresponds to the water that infiltrates in the soil. For difference, was obtained the water that was retained in the dossal. Statistical analysis the variance analysis, with regression in level of 5%. Water retention in the initial phase of corn was larger in the soil, for all straw amounts, and, in the final phase, water retention in plants dossal was increased. The largest water retention in straw was with 6 t ha-1, being the largest retention in the spacing of 45 cm among rows. In the dossal, the retention was smaller in the beginning and larger at the end, with the plants development (larger leaf area index). In the soil, water retention was larger where there was less straw in the initial phase. The retention was larger where there was more straw covering and in the smallest spacing (45 cm), being the soil retention larger without covering and with 75 cm among lines. In the dossal, retention was larger in the spacing 45 cm. In the black bean, water retention in straw was larger in the initial phase and with larger amount of straw, and in soil the largest water retention happened without covering (7,4mm). In the plants dossal water retention increased according to crop development.